Reasons for nonadherence to vaccination for influenza among older people in Brazil. - Aldiane Gomes de Macedo Bacurau (Public Library of Science (PLoS), 2021)
This study aimed to estimate the prevalence of non-vaccination and the reasons for nonadherence to the influenza vaccine among older Brazilians according to sociodemographic characteristics. A cross-sectional study was conducted with data from older people (≥ 60 years of age; n = 23,815) who participated in the 2013 National Health Survey. Frequencies of non-vaccination and the main reasons for nonadherence were calculated with respective 95% confidence intervals. The prevalence of non-vaccination was 26.9% (approximately 7,106,730 older people). The reason rarely gets the flu was the most cited among the men (28.2%), the 60-to-69-year-old age group (29.6%), individuals with higher education (41.9%), and those with health insurance (32.3%). Fear of a reaction was the most cited reason in the northeastern region (25.4%), among women (29.3%), longer-lived individuals (≥70 years; 28.7%), and those who did not know how to read/write (26.7%). A total of 12.1% reported not believing in the vaccine's protection, and 5.5% did not know that it was necessary to take vaccine. The proportions of the main reasons for non-vaccination varied by sociodemographic characteristics. This study's findings highlight the need to increase older people's knowledge regarding influenza and influenza vaccines. Healthcare providers should be encouraged to counsel older people-especially those in subgroups with lower adherence, such as residents in the Northeast region, those aged 60-69 years, those who do not know how to read/write, those without a spouse/companion, and those without health insurance-regarding the different aspects of the vaccine and formally indicate it for groups at risk.